2018
DOI: 10.1021/acs.biochem.8b00642
|View full text |Cite
|
Sign up to set email alerts
|

NMR Measurements Reveal the Structural Basis of Transthyretin Destabilization by Pathogenic Mutations

Abstract: Inherited mutations of transthyretin (TTR) destabilize its structure, leading to aggregation and familial amyloid disease. Although numerous crystal structures of wild-type (WT) and mutant TTRs have been determined, they have failed to yield a comprehensive structural explanation for destabilization by pathogenic mutations. To identify structural and dynamic variations that are not readily observed in the crystal structures, we used NMR to study WT TTR and three kinetically and/or thermodynamically destabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…The NMR backbone chemical shift assignment of wild type TTR has previously been reported under non-physiological pH and temperature conditions 16 and a new assignment at neutral pH has recently been deposited in the bmrb databank. 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR backbone chemical shift assignment of wild type TTR has previously been reported under non-physiological pH and temperature conditions 16 and a new assignment at neutral pH has recently been deposited in the bmrb databank. 17…”
Section: Resultsmentioning
confidence: 99%
“…L55 is located opposite to K48; A120 is involved in the intermolecular pairing between strands H and H′; and V121 forms an intramolecular H-bond with T106 of the facing strand G. Evidence from 19 F NMR also suggests that A120, together with F87, may additionally be critical for TTR stabilization as shown by the A120L TTR variant favoring a mis-packed state. 17…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Since the monomeric concentration of both Y69H, as well as F64S, is very low under native conditions this strongly suggests a partial exposure of the TTR polypeptide that normally is buried within its native fold. The occurrence of such partial unfolding is supported by previous studies using nuclear magnetic resonance (NMR) where a different surface exposure between different tetrameric variants of TTR has been shown using both Hydrogen-Deuterium (H/D) exchange [ 75 ] and relaxation dispersion experiments [ 76 , 77 ]. The exposure of normally hidden parts of TTR has also been shown using the conformational specific antibody MAB (39–44) , which normally only binds to unfolded TTR or its amyloid fold but where a strong reactivity is obtained to the tetrameric form of Y78F [ 78 ].…”
Section: Discussionmentioning
confidence: 74%
“…The acidification of solution triggers the flexible loop region between A and B to interact with A strand, leading to conformational changes occurring in the inner core domain ( Lim et al, 2016 ). The impact of single amino acid mutation on the stability of native TTR tetramer is attributed to a propagation of structural perturbation from the mutation site to the entire inner/outer ß -sheet domains ( Leach et al, 2018 ). The transmission electron micrographs showed that the TTR amyloid aggregates are rigid and unbranched fibrils with several micrometers in length and 70 to 130 Å in diameter ( Serpell et al, 1995 ).…”
Section: The Structural Conversion Of Ttr Amyloidogenesismentioning
confidence: 99%